Grand Strategy for India : 2020 and beyond - International Conference on India's National Security Strategy (2010 : New Delhi, India); Krishnappa, Venkatshamy; George, Princy; Institute for Defence Studies and Analyses (New Delhi, India) (New Delhi : Institute for Defence Studies and Analyses : Pentagon Security International, 2012)
Papers presented at the four-day international conference on India's national security strategy, held at Institute for Defence Studies & Analyses during 20-23 December 2010.
Includes bibliographical references and index
Keywords: National security -- India -- Congresses; India -- Strategic aspects -- Congresses